Análise do conhecimento e das atitudes frente às fontes renováveis de energia: uma contribuição da Psicologia - Pessoa, Viviany Silva (2011)
The present thesis aimed at verifying knowledge and attitudes toward renewable energy sources (RES), solar and wind energy, and in what extent these attitudes are related and can be predicted by environmental inclusion and human values. Study 1 aimed to verify the knowledge about RES. Participants were 74 people (27 men and 47 women) from João Pessoa (PB), with ages between 18 and 61, most were undergraduate from public universities. They answered to the self-report technique known as Natural Semantic Networks (NSN), besides questions about the knowledge of RES and demographic issues. An exploratory analysis identified semantic networks that, despite showing a limited repertory of solar and wind energy, represented knowledge with positive meaning, useful and coherent with the proposal of efficient and sustainable use of energy. In these semantic networks, the knowledge about solar and wind energy are represented by words that match with the pro-environmental appeal (e.g. nature and clean), words that show the technological features (e.g. technology and strength) and also the economic aspect (e.g. sustainable, economy and production). Study 2 aimed to develop an attitude toward RES instrument, with versions to solar, wind and conventional energy, besides verifying psychometric parameter of three other measures: Environmental Attitudes Inventory, Nature Relatedness Questionnaire and Connectedness to Nature Scale. Participants were 204 people from João Pessoa (PB), with mean age of 23 years old (sd = 13.83), most female (60%). Exploratory analysis and calculation of internal consistency used for the three versions indicated structures of EAFRE unifatorial with Crombach s alphas of 0.94 to Solar version, 0.93 to Wind version, and 0.86 for the conventional version. The exploratory and confirmatory analysis, as well as the calculation of internal consistency used in the validation of other measures parameters indicated adequate validity and reliability. In Study 3, we tested the hypothesis related to the objectives of the thesis, providing subsidies for the construction of the theoretical model values including environmental attitude behavior. 282 internet users participated, mean age 30 years (sd = 11.60), mostly female (65%). The hypotheses were corroborated listed, except for hypothesis 3 and hypothesis 4. However, despite these results, it was possible to propose an explanatory model in which human values are the underlying attitudes to renewable energy. One trusts that this thesis contributes to the literature of social and environmental psychology, presenting psychometric parameters of measures that can be used in future studies, and contributes with an explanatory model of the acceptance behavior of RES. Through this model, it is possible to develop incentive marketing strategies and public policies toward the use of renewable energy sources.